A Novel Matching of MR Images Using Gabor Wavelets - Akinlar, Mehmet Ali; Kurulay, Muhammet; Secer, Aydin; Celenk, Mehmet (TAYLOR & FRANCIS LTD, 2013)
This study introduces a hybrid method for deformable matching of Magnetic resonance (MR) images by utilizing the advantages of both wavelets and variational calculus. Image matching problem is expressed as an optimal control problem and discretization of the resulting Euler-Lagrange equations is written in terms of the system of linear equations in the form of Au = f, where u is the image displacement field. Implementation of the algorithm exploits Gabor wavelet energy maps of MR images. The proposed algorithm provides an efficient MR matching technique. Experimental results proved that the method can match MR images better than the only variational or only wavelet-based methods.
Keywords: Gabor wavelets; Image matching; Magnetic resonance imaging; Engineering; Telecommunications